2022
DOI: 10.1108/ijbm-02-2022-0052
|View full text |Cite
|
Sign up to set email alerts
|

Exploring country differences in the adoption of mobile payment service: the surprising robustness of the UTAUT2 model

Abstract: PurposeThis paper investigated the extent to which the predictive power of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) was robust against cultural variations and to what extent its predictive power could be improved by including face-valid individual differences (i.e. perceived risk and personal innovativeness) and cultural factors (i.e. individualism and uncertainty avoidance).Design/methodology/approachData were collected from web surveys of Chinese, American and Belgian mobile Internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…Previous studies have predicted that technology anxiety is a moderator in consumer and brand relationships where technology is involved (Lee and Lyu, 2019). If consumers find it challenging to use a MAR app, they may not adopt the technology (Meuter et al, 2003;Wu and Liu, 2023). In Pakistan, technology-related anxiety is prevalent due to various factors.…”
Section: Augmented Reality Is the New Digital Bankingmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have predicted that technology anxiety is a moderator in consumer and brand relationships where technology is involved (Lee and Lyu, 2019). If consumers find it challenging to use a MAR app, they may not adopt the technology (Meuter et al, 2003;Wu and Liu, 2023). In Pakistan, technology-related anxiety is prevalent due to various factors.…”
Section: Augmented Reality Is the New Digital Bankingmentioning
confidence: 99%
“…If consumers find it challenging to use a MAR app, they may not adopt the technology (Meuter et al. , 2003; Wu and Liu, 2023). In Pakistan, technology-related anxiety is prevalent due to various factors.…”
Section: Introductionmentioning
confidence: 99%
“…While during the research (Hasan & Ahmet, 2022), the study participants had exposure in using WeChat pay the participants did engage in payment's despite they had the predictions that the platforms be unsecured or not secure. Journal of Service Science and Management Wu and Liu (2022), the researchers found that the UTAUT2 model was less predictive in the country where the adoption of mobile payment services is high (i.e. China).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Previous research on the relationship between social influence and intention produced conflicting results. Sukwadi et al (2022), Suo et al (2022), and Wu and Liu (2022) discovered a relationship between social influence and consumers' intention to use QR code mobile payment. Ghaisani et al (2022), Hajazi et al (2021), Imani and Anggono (2020), and Shane et al (2022) found opposite results.…”
Section: Social Influencementioning
confidence: 99%